Virtual and Augmented Reality
DOI: 10.4018/978-1-5225-5469-1.ch042
|View full text |Cite
|
Sign up to set email alerts
|

Personal Touch

Abstract: Large format touch screens have become an important means of interaction for collaborative and shared environments. This type of display is particularly useful for public information display in museums and similar contexts. Similarly augmented reality displays have become popular in this context. Both systems have benefits and drawbacks. Personal Touch is an augmented-reality display system combining real objects with superimposed interactive graphics. With increasing display sizes and users moving in front of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The 2-weekold seedlings were more susceptible than the 5-week-old plants. In studies of tomatoes on the island of Hawaii, rain of low pH was found to decrease pollen germination and pollen tube growth 10 c a 0 :Pz 0 a and generally lower the quality and production of these plants (23). Toxic effects on plants may be associated with the increased proportions of HSO3ions and undissociated H2SO3 at low pH (24).…”
mentioning
confidence: 99%
“…The 2-weekold seedlings were more susceptible than the 5-week-old plants. In studies of tomatoes on the island of Hawaii, rain of low pH was found to decrease pollen germination and pollen tube growth 10 c a 0 :Pz 0 a and generally lower the quality and production of these plants (23). Toxic effects on plants may be associated with the increased proportions of HSO3ions and undissociated H2SO3 at low pH (24).…”
mentioning
confidence: 99%